2011
DOI: 10.1007/s11524-010-9510-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clustering of HIV Prevalence in Atlanta, Georgia and Population Characteristics Associated with Case Concentrations

Abstract: We assessed prevalent HIV cases in Atlanta to examine case distribution trends and population characteristics at the census tract level that may be associated with clustering effects. We calculated cluster characteristics (area and internal HIV prevalence) via Kuldorff's spatial scan method. Subsequent logistic regression analyses were performed to analyze sociodemographics associated with inclusion in a cluster. Organizations offering voluntary HIV testing and counseling services were identified and we assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 30 publications
1
63
0
Order By: Relevance
“…The high AIDS incidence, which was observed in the metropolitan region of the State of Rio de Janeiro, can also be seen in other metropolitan areas, such as in some populated urban regions of South Africa (Manda et al, 2012), the metropolitan area of Atlanta (Hixson, 2011) and another 11 large urban areas in the United States of America (Hall et al, 2010). In 2011, the AIDS incidence in Brazil was 20.2 cases per 100,000.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The high AIDS incidence, which was observed in the metropolitan region of the State of Rio de Janeiro, can also be seen in other metropolitan areas, such as in some populated urban regions of South Africa (Manda et al, 2012), the metropolitan area of Atlanta (Hixson, 2011) and another 11 large urban areas in the United States of America (Hall et al, 2010). In 2011, the AIDS incidence in Brazil was 20.2 cases per 100,000.…”
Section: Discussionmentioning
confidence: 91%
“…The Metropolitan Rio de Janeiro area has hundreds of low-income communities and some studies indicate that higher AIDS incidence tend to occur in poorer neighbourhoods (Greco and Simão, 2007;Hixson et al, 2011;Shacham et al, 2013;da Silva Pires Araujo et al, 2014). It has been suggested that poverty may increase the vulnerability to HIV infection since it hinders access to information, preventive measures and healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, the authors describe a geostatistical framework for designing a novel treatment as prevention (TasP) for HIV elimination strategy (2). They make the argument that reaching the UNAIDS goals of 90-90-90 (diagnosed-treated-virologically suppressed) may be quite difficult in some rural communities.…”
mentioning
confidence: 99%
“…We have previously applied geospatial clustering techniques to analyze the local HIV prevalence in Atlanta, Georgia, USA and identified that there are areas within urban areas that could be characterized as having a generalized HIV epidemic according to the World Health Organization definition at the time (2). Given the severity of the HIV epidemic in the Southern US, we used geospatial techniques to demonstrate the feasibility of reaching urban "hidden populations" who were highly susceptible to HIV in order to meet HIV prevention and treatment priorities (3).…”
mentioning
confidence: 99%